{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# hw7 - Granillo Yvette Homework 7 Due 3:00 am Inst Edward...

This preview shows pages 1–4. Sign up to view the full content.

Granillo, Yvette – Homework 7 – Due: Oct 13 2005, 3:00 am – Inst: Edward Odell 1 This print-out should have 21 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = 2 x sin 5 x + 2 5 cos 5 x. 1. f 0 ( x ) = 10 x cos 5 x correct 2. f 0 ( x ) = 10 x cos 5 x + 4 sin 5 x 3. f 0 ( x ) = 10 x cos 5 x - 4 sin 5 x 4. f 0 ( x ) = 10 cos 5 x 5. f 0 ( x ) = - 10 x cos 5 x Explanation: Since d dx sin x = cos x, d dx cos x = - sin x, it follows that f 0 ( x ) = 2 sin 5 x + 10 x cos 5 x - 2 sin 5 x. Consequently, f 0 ( x ) = 10 x cos 5 x . keywords: Stewart5e, 002 (part 1 of 1) 10 points Find f 0 ( x ) when f ( x ) = x - 1 x + 1 · 2 . 1. f 0 ( x ) = - 4( x + 1) ( x - 1) 3 2. f 0 ( x ) = - 4( x - 2) ( x + 1) 3 3. f 0 ( x ) = 6( x - 2) ( x + 1) 3 4. f 0 ( x ) = 4( x - 1) ( x + 1) 3 correct 5. f 0 ( x ) = - 6( x + 2) ( x - 1) 3 6. f 0 ( x ) = 6( x + 1) ( x - 1) 3 Explanation: By the Chain and Quotient Rules, f 0 ( x ) = 2 x - 1 x + 1 · ( x + 1) - ( x - 1) ( x + 1) 2 . Consequently, f 0 ( x ) = 4( x - 1) ( x + 1) 3 . keywords: Stewart5e, 003 (part 1 of 1) 10 points Determine f 0 ( x ) when f ( x ) = 1 + x 1 - 2 x 2 . 1. f 0 ( x ) = - 1 - 2 x (1 - 2 x 2 ) 1 / 2 2. f 0 ( x ) = - 1 + 2 x (1 - 2 x 2 ) 1 / 2 3. f 0 ( x ) = 1 + 2 x (1 - 2 x 2 ) 1 / 2 4. f 0 ( x ) = - 1 + 2 x (1 - 2 x 2 ) 3 / 2 5. f 0 ( x ) = 1 + 2 x (1 - 2 x 2 ) 3 / 2 correct 6. f 0 ( x ) = 1 - 2 x (1 - 2 x 2 ) 3 / 2

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Granillo, Yvette – Homework 7 – Due: Oct 13 2005, 3:00 am – Inst: Edward Odell 2 Explanation: By the Product and Chain Rules, f 0 ( x ) = 1 (1 - 2 x 2 ) 1 / 2 + 4 x (1 + x ) 2(1 - 2 x 2 ) 3 / 2 = (1 - 2 x 2 ) + 2 x (1 + x ) (1 - 2 x 2 ) 3 / 2 . Consequently, f 0 ( x ) = 1 + 2 x (1 - 2 x 2 ) 3 / 2 . (Note: the Quotient Rule could have been used, but it’s simpler to use the Product Rule.) keywords: Stewart5e, 004 (part 1 of 1) 10 points Determine f 0 ( x ) when f ( x ) = 2 cos 2 x + 3 sin 2 x . 1. f 0 ( x ) = - 4 sin x - 6 cos x 2. f 0 ( x ) = 2 sin x cos x correct 3. f 0 ( x ) = - 10 sin x cos x 4. f 0 ( x ) = 4 cos x + 6 sin x 5. f 0 ( x ) = - 2 sin x cos x 6. f 0 ( x ) = - 4 sin x + 6 cos x 7. f 0 ( x ) = 10 sin x cos x Explanation: Since d dx sin x = cos x , d dx cos x = - sin x , the Chain Rule ensures that f 0 ( x ) = - 4 cos x sin x + 6 sin x cos x . Consequently, f 0 ( x ) = 2 sin x cos x . keywords: Stewart5e, 005 (part 1 of 1) 10 points Find the value of f 0 (1) when f ( x ) = ( x 2 + 8) 1 / 2 + 1 x . 1. f 0 (1) = - 1 3 2. f 0 (1) = 2 3 3. f 0 (1) = 0 4. f 0 (1) = - 2 3 correct 5. f 0 (1) = 1 3 Explanation: Using the Chain Rule and the fact that d dx x r = r x r - 1 holds for all values of r , we see that f 0 ( x ) = x ( x 2 + 8) 1 / 2 - 1 x 2 . At x = 1, therefore, f 0 (1) = - 2 3 . keywords: Stewart5e, 006 (part 1 of 1) 10 points Find the derivative of f when f ( x ) = 1 4 (3 - 4 x ) 3 + 8 x .
Granillo, Yvette – Homework 7 – Due: Oct 13 2005, 3:00 am – Inst: Edward Odell 3 1. f 0 ( x ) = - 4 x 3 + 8 x 2. f 0 ( x ) = - 12 x 3 + 8 x correct 3. f 0 ( x ) = - 12 x 3 + 4 x 4. f 0 ( x ) = 12 x 3 + 8 x 5. f 0 ( x ) = 4 x 3 + 8 x Explanation: By the Product and Chain Rules, f 0 ( x ) = - 3 + 8 x + 3 - 4 x 3 + 8 x .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 10

hw7 - Granillo Yvette Homework 7 Due 3:00 am Inst Edward...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online